Foggy Video Restoration Using Guided Filter - Kanala, Mounika; Mahaboob, Shaik Taj (International Journal of Computer Sciences and Engineering, 2025)
When videos are captured under the influence of atmospheric or climatic conditions, the overall quality of the image gets effected with fog and haze. This work focuses on haze removal which is also called as the visibility restoration which can infer to the various procedures employed for removing or reducing degradation from the image. Degradation in image can be due to various reasons such as miss-focus, relative atmospheric conditions and object-camera motion. This paper presents a method in which the fog in video can be removed by using dark channel method followed by Guided filtering. Guided filter has better filtering capability, fast running time and gives a clear haze free video. So, we can say that this method can be employed in real-life settings or video applications. Restoration of hazy videos is important in computer graphics, remote sensing and outdoor surveillance